Introducing a novel approach to dental color reproduction using AI technology - Awdaljan, Marat Wartanovic; Roque, João Carlos; Choi, James; Rondón, Luis Felipe [UNESP] (Wiley, 2024)
Objective: This article aims to describe a systematic method for tooth color reproduction with ceramics restorations employing artificial intelligence (AI) software named Matisse. It provides a comprehensive analysis of the entire process, beginning with shade-taking and extending to ceramic application in a complex clinical case in the anterior region—specifically, a single central restoration supported by an implant. Clinical Considerations: The clinical case presented highlights the potential of Matisse software for generating ceramic (inSync-Jensen Dental, USA) and staining (Miyo-Jensen Dental, USA) recipes over a zirconia abutment (Katana-Noritake Dental, Japan). This approach achieves an optimal single central restoration utilizing CAD-CAM and layering techniques. Conclusions: The systematic method employing the Matisse software achieved accurate color reproduction for a single central restoration supported by an implant. This result was achieved by the dental ceramist within the first attempt and without seeing the patient in the entire process. Clinical Significance: The Matisse AI-assisted protocol offers a systematic and scientifically grounded method for color reproduction in dentistry for indirect restorations.
Keywords: artificial intelligence; CAD/CAM; dental ceramics; dental color; dental technology; digital dentistry